2019
DOI: 10.1126/science.aav2546
|View full text |Cite
|
Sign up to set email alerts
|

The sleep-wake cycle regulates brain interstitial fluid tau in mice and CSF tau in humans

Abstract: The sleep-wake cycle regulates interstitial fluid (ISF) and cerebrospinal fluid (CSF) levels of β-amyloid (Aβ) that accumulates in Alzheimer’s disease (AD). Furthermore, chronic sleep deprivation (SD) increases Aβ plaques. However, tau, not Aβ, accumulation appears to drive AD neurodegeneration. We tested whether ISF/CSF tau and tau seeding and spreading were influenced by the sleep-wake cycle and SD. Mouse ISF tau was increased ~90% during normal wakefulness versus sleep and ~100% during SD. Human CSF tau als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
443
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(530 citation statements)
references
References 34 publications
21
443
2
2
Order By: Relevance
“…1 As such, disrupted SWS could result from degeneration of sleep regulatory brain regions affected in PD. 20 However, we consider our finding as preliminary due to limitations. These effects could be driven by SWS counteracting pathological protein accumulation through reduced production of alpha-synuclein owing to lower neurometabolic activity 5,6 or promotion of glymphatic clearance.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…1 As such, disrupted SWS could result from degeneration of sleep regulatory brain regions affected in PD. 20 However, we consider our finding as preliminary due to limitations. These effects could be driven by SWS counteracting pathological protein accumulation through reduced production of alpha-synuclein owing to lower neurometabolic activity 5,6 or promotion of glymphatic clearance.…”
Section: Discussionmentioning
confidence: 86%
“…4 Although, in contrast to beta-amyloid, alpha-synuclein primarily accumulates intracellularly, glymphatic clearance could theoretically slow its extracellular propagation, 19 and novel evidence suggests that sleep-wake dynamics might regulate levels of alphasynuclein in cerebrospinal fluid. 20 However, we consider our finding as preliminary due to limitations. Owing to the retrospective study design, we observed data variability (eg, 31 of 129 patients were drugnaive at baseline and none at follow-up).…”
Section: Discussionmentioning
confidence: 86%
“…From this follows that sleep might be required for "waste" removal from the brain. In addition, levels of ISF and CSF tau relate to neuronal activity and the sleep-wake cycle rather than to paravascular clearance [71]. The role of Aqp4 in glymphatic function is, however, still a matter of discussion.…”
Section: Paravascular Flowmentioning
confidence: 99%
“…Sleep disturbance and insomnia are common in Alzheimer's disease (AD), affecting ≈40% of patients . There is emerging evidence that poor sleep may contribute to the development of AD and impair memory function . Options for effective pharmacological treatment of insomnia in AD are limited, with inconsistent or poor‐quality evidence for efficacy of melatonin, second‐generation antipsychotics (which are primarily used to target other neuropsychiatric and behavioral symptoms associated with AD), and sedating antidepressants .…”
Section: Introductionmentioning
confidence: 99%
“…1 There is emerging evidence that poor sleep may contribute to the development of AD and impair memory function. [2][3][4][5][6][7][8][9] Options for effective pharmacological treatment of insomnia in AD are limited, with inconsistent or poor-quality evidence for efficacy of melatonin, [10][11][12][13] second-generation antipsychotics (which are primarily used to target other neuropsychiatric…”
Section: Introductionmentioning
confidence: 99%